Pedagogical practices in enriching students’ cultural experiences: The case of private schools in the Philippines - Helen Bihag Boholano; Remedios Cabaral Bacus; Bernard Evangelicom Valen Jamon (Ho Chi Minh City Open University Journal of Science - Social Sciences)
This study analyzes the pedagogical preferences of private basic education institutions in Cebu, Philippines, in enriching learners’ cultural knowledge and experiences. A total of 53 teachers and school administrators from selected private basic education institutions in Cebu, Philippines, were the participants in the study. A sequential explanatory mixed method design was utilized to investigate the profile of the academic institutions, pedagogical practices, and plans for cultural education. Findings revealed the institutions’ varied pedagogical practices to promote cultural awareness and appreciation. Furthermore, it acknowledges the influence of external providers in enriching the learners’ cultural experiences. The themes “much can be done” and “need for partnerships” emphasize the importance of partnerships among institutions in connecting with local cultural arts centers and museums to promote cultural education. The study provides valuable insights into how private institutions approach cultural education and their strategies to promote cultural awareness and appreciation among learners. It sheds light on the need for innovative approaches to cultural education in the current context by strengthening partnerships with cultural centers in developing and sharing technology-based teaching and learning materials.